MENILIK KEBIJAKAN PEMBANGUNAN PERTANIAN - Aziza, Tri Noor (Pusjar SKPP Lembaga Administrasi Negara, 2009)
To establish agriculture as a leading sector through a planned, systematic and remain accommodating the existing condition process, a formula is needed to be the framework in preparing the agricultural policy. There are four main components in the framework of agricultural policy, there are : objectives that is expected to be achieved by the policy makers, constraints that limit the results that can be achieved, policies which consist of instruments that are used by the government to change the agricultural outcomes, and the implemented strategies through a well-coordinated policy implementation. It is expected that through the understanding of the agricultural framework, the policy makers can make the appropriate policies to accomplish the vision and mission of agricultural development Keywords : agriculture, framework, development